Physical rehabilitation in complex therapy of the ureter stones patients in the Truskavets health resort area - Shologon R.P (Kharkov National Pedagogical University, 2010)
Efficiency of rehabilitation measures is considered in complex therapy with the use of differentiated methods of medical physical education for patients with stones of ureter. Under a supervision there was 143 patients. 93 patients were made basic group, 50 patients - control. From them 51 (56 %) are men and 42 (54%) are women. Age of patients made from 20 to 60 years. A sanatorium-resort rehabilitation is recommended with the use of the differentiated methods of medical gymnastics. Application of method improved the indexes of the functional state of buds and overhead urinary ways. Frequency of advancement and output of concrements is also megascopic.